Long distance signalling and epigenetic changes in crop grafting - Jeynes-Cupper, Katie; Catoni, Marco (Frontiers in Plant Science, 2023)
Humans have used grafting for more than 4000 years to improve plant production, through physically joining two different plants, which can continue to grow as a single organism. Today, grafting is becoming increasingly more popular as a technique to increase the production of herbaceous horticultural crops, where rootstocks can introduce traits such as resistance to several pathogens and/or improving the plant vigour. Research in model plants have documented how long-distance signalling mechanisms across the graft junction, together with epigenetic regulation, can produce molecular and phenotypic changes in grafted plants. Yet, most of the studied examples rely on proof-of-concept experiments or on limited specific cases. This review explores the link between research findings in model plants and crop species. We analyse studies investigating the movement of signalling molecules across the graft junction and their implications on epigenetic regulation. The improvement of genomics analyses and the increased availability of genetic resources has allowed to collect more information on potential benefits of grafting in horticultural crop models. Ultimately, further research into this topic will enhance our ability to use the grafting technique to exploit genetic and epigenetic variation in crops, as an alternative to traditional breeding.